Bridging Technology And Financial Competence: A Study On Digital Payment Behavior Among Tourists - Pudin Saepudin; Nenden Dianawati; Endang Komesty Sinaga; Misran (Politeknik Negeri Bandung, 2026)
While digital payment systems have become ubiquitous in tourism, traditional adoption models often overlook the critical role of personal competencies in mature digital ecosystems. This study investigates the impact of self-efficacy and perceived financial literacy (PFL) on digital payment adoption and evaluation among travelers. Using an integrative framework combining TAM, DOI, and UTAUT, and grounded in Social Signaling Theory, data were collected from 495 Indonesian tourists and analyzed via PLS-SEM. The results reveal a significant paradigm shift: traditional drivers such as relative advantage and observability are non-significant, suggesting a